2018
DOI: 10.1002/ajh.25202
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of end‐organ disease and earlier mortality in adults with sickle cell disease: A retrospective‐prospective cohort study

Abstract: Chronic end-organ complications result in morbidity and mortality in adults with sickle cell disease (SCD). In a retrospective-prospective cohort of 150 adults with SCD who received standard care screening for pulmonary function abnormalities, cardiac disease, and renal assessment from January 2003 to 2016, we tested the hypothesis that clustering of end-organ disease is common and multiple organ impairment predicts mortality. Any end-organ disease occurred in 59.3% of individuals, and 24.0% developed multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 56 publications
0
40
0
Order By: Relevance
“…Although most patients with SCD in resource-rich countries live beyond childhood, the median life expectancy remains low, and is reduced by 2 to 3 decades [8]. This increased risk of early mortality is, in large part, due to the development of multiple end-organ damage [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Although most patients with SCD in resource-rich countries live beyond childhood, the median life expectancy remains low, and is reduced by 2 to 3 decades [8]. This increased risk of early mortality is, in large part, due to the development of multiple end-organ damage [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As patients with SCD grow older, they develop end-organ damage related to vascular complications, including pulmonary hypertension, diastolic left heart disease, and nephropathy. 1 More than 50% of adult patients have dysfunction of at least one organ system, and 25% have multi-organ dysfunction. Simultaneous endorgan disease in heart, lung and kidney increased mortality by approximately 4-fold.…”
Section: Validation Of a Composite Vascular High-risk Profile For Adumentioning
confidence: 99%
“…Simultaneous endorgan disease in heart, lung and kidney increased mortality by approximately 4-fold. 1 Intravascular hemolysis contributes to pulmonary vasculopathy and renal insufficiency by elaboration of free hemoglobin, which produces redox stress, inflammation, hypercoagulability, and vascular injury. 2 We have reported that elevated tricuspid regurgitation velocity (TRV), a non-invasive marker of elevated systolic pulmonary artery pressure, is associated with an increased risk of death in two independent cohorts.…”
Section: Validation Of a Composite Vascular High-risk Profile For Adumentioning
confidence: 99%
See 2 more Smart Citations